The influence of rodenticides in dissemination of endoparasites of dogs and cats - LEFKADITIS, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Mice and other rodents are well known to play an important role in the biological cycle of many parasites of pets. Among the endoparasites identified in Greece which could be transmitted to dogs and/or cats from colloquially rodents are Spirocerca lupi, Ascaridae namely Toxocara canis, Toxascaris leonina in dogs and Ancylostoma caninum, A.braziliense, Trichinella spiralis, Echinococcus granulosus, Toxoplasma gondii, Cryptosporidium spp and Leihsmania spp, while cats can be infested by Toxocara cati, Toxascaris leonina, Ancylostoma tubaeformae, A.braziliense, Aelurostrongylus abstrusus and Taenia taeniaformis, Toxoplasma gondii, Cryptosporidium spp and Leihsmania spp. The route of infection of pet includes in many cases ingestion of parasite infested rodents. A number of these parasites are also of great Public Health importance because they are causing zoonotic diseases. Because of the large numbers of rodents in some areas and their role in transmitting diseases in man and animals, rodenticide programs are performed by individuals or state agencies. Rodenticides are chemical and non-chemical compound which are used to eliminate rodents. However, attention should be paid on their use and manufacturer’s instructions should be strictly followed because of the risk of accidental poisoning of pets and children. It can be conclude that prudent rodent control is essential in the prevention of parasite infection of pets and the transmission of zoonotic parasite to humans.